2008
DOI: 10.1111/j.1741-3737.2008.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Choice of Surname Upon Marriage in Norway

Abstract: This study examines women’s choice of surname upon marriage, using a nationally representative Norwegian sample (N= 1,276). Regression analyses revealed that age at marriage, own and mother’s education, urban residence, importance of paid labor, liberal family values, and egalitarian work‐family roles positively influence marital name keeping. Women’s increasing education and economic independence and changes in marriage and the social institution of the family suggest a rising likelihood of name keeping over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 25 publications
2
41
1
1
Order By: Relevance
“…In our study we found that women who married in Jewish or Catholic ceremonies married at a younger age than women who married in Protestant ceremonies and they in turn married at an earlier age than women who married in civil or Nondenominational ceremonies. Several studies have found that the older a woman is at the time of marriage, the more likely she is to keep her birth name (Brightman, 1994;Goldin & Shim, 2004;Johnson & Scheuble, 1995;Lillian, 2009;Noack & Wiik, 2008). Our data are consistent with that finding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study we found that women who married in Jewish or Catholic ceremonies married at a younger age than women who married in Protestant ceremonies and they in turn married at an earlier age than women who married in civil or Nondenominational ceremonies. Several studies have found that the older a woman is at the time of marriage, the more likely she is to keep her birth name (Brightman, 1994;Goldin & Shim, 2004;Johnson & Scheuble, 1995;Lillian, 2009;Noack & Wiik, 2008). Our data are consistent with that finding.…”
Section: Discussionsupporting
confidence: 91%
“…One reason for this increased age at first marriage is the increased educational aspirations (Thornton et al, 1995) and increased workplace opportunities for women in the labor market (Thornton et al, 1995). Apart from the association between names, educational attainment, and professional standing, previous studies have found that the older a woman is at the time of marriage, the greater the identification with her name and the greater the motivation to keep that name (Brightman, 1994;Goldin & Shim, 2004;Johnson & Scheuble, 1995;Lillian, 2009;Noack & Wiik, 2008). We therefore hypothesized that older women would be more likely to keep their birth names, independent of religion and time period.…”
Section: Hypothesis 3 Influence Of Religion On Name Keeping As a Funmentioning
confidence: 99%
“…Although Canadians and Americans share many similarities, Canadian social policies tend to be somewhat more liberal (e.g., Olsen 2007); as a result, it is possible that Canadian preferences for last names may be somewhat different, with a weaker preference for traditional choices. Countries with more egalitarian values, such as Norway, have shown a significant increase in the number of women keeping their birth surnames in recent years (Noack and Wiik 2008). Because the present studies involved nonrepresentative samples of Canadians, however, it is not possible to draw firm conclusions regarding possible crossnational differences.…”
Section: Discussionmentioning
confidence: 92%
“…Few people seem to know that, according to the law, cohabiting couples, whether they have common children or not, can change to a shared surname in the same way as married couples (Noack and Wiik 2008). How many cohabiting couples are sharing one surname is unknown, but it does seem to be rather rare.…”
Section: With the Same Surname You Become A Little Family Belonging mentioning
confidence: 99%